Young Children’s Eating in the Absence of Hunger: Links With Child Inhibitory Control, Child BMI, and Maternal Controlling Feeding Practices - Philippe, Kaat; Chabanet, Claire; Issanchou, Sylvie; Monnery-Patris, Sandrine (Frontiers in Psychology, 2021)
This study aimed to gain a better understanding of the associations between young children’s eating in the absence of hunger (EAH), inhibitory control, body mass index (BMI) and several maternal controlling feeding practices (food as reward, restriction for health, restriction for weight control). In addition, to more properly assess the relationship between children’s and maternal variables, the link between EAH and restriction was explored separately in two directionalities: “child to parent” or “parent to child”. To do this, mothers of 621 children aged 2.00-6.97 years (51% boys, M = 4.11 years, SD = 1.34) filled in a questionnaire with items from validated questionnaires. Structural equation modeling was used to analyze the data. The results showed, whatever the directionality considered, a positive association between children’s eating in the absence of hunger and their BMI z-scores. Restriction for health and restriction for weight control were differently linked to EAH and to children’s BMI z-scores. Namely, low child inhibitory control, food as reward and restriction for health were identified as risk factors for EAH. Restriction for weight control was not linked to EAH, but was predicted by child BMI z-scores. Interventions aiming to improve children’s abilities to self-regulate food intake could consider training children’s general self-regulation, their self-regulation of intake, and/or promoting adaptive parental feeding practices.